The role of HIV-1 Gag and genomic RNA interactions in virion assembly - Koma, Takaaki; Le, Bao Quoc; Tran, Khanh Quoc; Doi, Naoya; Kondo, Tomoyuki; Miyakawa, Kei; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2025)
The virion assembly represents a critical aspect of producing infectious progenies required for HIV-1 replication. Each step in that process, such as Gag-membrane binding, Gag-genomic RNA binding/packaging, Gag multimerization, and viral particle budding, has been extensively analyzed in a stepwise and specific manner. While Gag proteins are the primary drivers of HIV-1 virion assembly, the interactions between Gag and RNA play a significant role in regulating the process. This article provides an updated overview and perspective on HIV-1 virion assembly, with a particular focus on the role of Gag-RNA interactions.